Measuring Knowledge Spillovers Using Patent Citations: Evidence from the Belgian Firm's Data - Ruslan Lukach; Joseph Plasmans (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper conducts a comprehensive study of patent citations in patents granted to Belgian corporate applicants by the United States and the European Patent Offices using qualitative response variable analysis. The analysis uncovered different patterns of citations in patents, which belong to different industrial classes. The studied citation data provides evidence of inter- or intra-firm and inter- or intra-industry knowledge spillovers, which are quite industry specific. In the framework of R&D cooperation stimulating policies, our results advocate for considering those differences in order to balance the effect of knowledge spillovers driven market incentives and direct regulation.
Keywords: 330; knowledge spillovers; R&D; patent citation; limited dependent variable regression